An Independent Sensitive MEMS Thermal Expansion Flow Gyro - Liu, Junyu; Piao, Linhua; Zhang, Yan; Tong, Jiacheng; Ma, Xuanlin (IEEE ... Annual International Conference on Cyber Technology in Automation, Control, and Intelligent Systems (Online), 2023)
A single-axis MEMS thermal expansion flow gyro with an independent sensitive unit is proposed and the principle of independent sensitivity to improve gyro sensitivity is revealed. The temperature field inside the sensitive element of the independent sensitive gyro is calculated by using the finite element method. The calculation results show that (1) the sensitivity is improved from 1.07 K/rad/s to 2.43 K/rad/s compared with the conventional temperature sensitive method.(2) The optimal structural sensitivity of the gyro at angular velocities [0 rad/s, 10 rad/s] was 7.67 K/rad/s with a nonlinearity of 11.08% at a heater distance of 4 mm, an upper chamber height of 3 mm, and a heater power of 70 mW. The results provide a theoretical basis for the structural design and performance optimization of the thermal expansion flow gyro.